Integrative instruments in care systems in Latin America: a public policy perspective - Michel Sahagún, Cynthia Lorena; Cejudo Ramírez, Guillermo Miguel; Oseguera Gamba, Adriana Sofía (Revista del CLAD Reforma y Democracia, 2024)
Some Latin American governments have developed systems that seek to comprehensively guarantee the right to provide and receive care. These initiatives aim to recognize, redistribute, or reduce caregiving work within households by coordinating a set of policies, implemented by different agencies, around the same individual. Achieving this requires overcoming the challenge of intersectoral coordination, based on management instruments that allow interventions to be articulated around the diverse care needs of the population. Based on the policy integration literature, we conduct a comparative analysis of four emblematic care systems in the region using official data and semi structured interviews. In contrast to recent research that analyzes programs, services, and target populations, we focus on how systems manage to operate in a coordinated manner. We argue that building care systems requires the construction of instruments that ensure the integrated operation of the system around a person or territory. We examine how the deployment of specific decisions to guide the operation of care systems address a key contemporary challenge in public policy and administration: the coordinated operation of policy sectors around complex problems and the construction of comprehensive responses to multidimensional challenges.